Obstacles and barriers for measuring building’s circularity - Rahla, K. M. (2019)
Applying circular economy principles in the built environment at different levels is considered as a future vital approach to reducing its environmental impacts along with huge economic benefits, which is generally explained by ?decoupling resource consumption from economic development?. At the meso-level of the built environment, circular buildings have arisen as a more holistic approach to embrace circular economy thinking. This novel practice requires flexible and adaptable strategies to enable alteration and adjustment while avoiding material loss and keeping the value of products at the highest levels. Evaluating buildings circularity by means of standardized indicators is therefore primordial to implement a common language between all involved actors and monitoring the progress towards an eco-design. Still, the complexity of putting together such a methodology is far from being a mere task. To date, several studies have been more focused on assessing circularity for short-lived products while disregarding assessing long-lived products as buildings and their ability to be deconstructed and reassembled in a so-called ?reversible design?. Unfolding a set of robust indicators to measure building circularity promises to be challenging in order to set up a flawless assessment tool which can summarise different aspects of the application circular economy at a building level. This paper intends to put an emphasis on the potential obstacles that can be encountered while developing metrics to quantify building circularity.